Everychild - Dodge, Louis, 1870-1952; Laite, Blanche Fisher (Salt Lake City, UT : Project Gutenberg, 2006)
"Everychild: A story which the old may interpret to the young" by Louis Dodge is a children's tale written in the early 20th century. The narrative follows Everychild, a universal character representing all children, as he embarks on an extraordinary journey facing various challenges and adversaries, most notably the Giant Fear. Throughout his adventures, he encounters well-known figures from fairytales and folklore. The opening of the story introduces a domestic scene where Everychild struggles to connect with his indifferent parents. He is burdened by a damaged kite, symbolizing the children's desire for attention and affection. Notably, he soon encounters Father Time and a Masked Lady who represent guiding forces, setting the stage for his quest. As Everychild prepares to leave home, he is confronted by the Giant Fear, a manifestation of his anxieties, initiating the thematic exploration of bravery and self-discovery. The narrative unfolds with a blend of fantasy and life lessons, making it an engaging read for both children and adults. (This is an automatically generated summary.)
Release date is 2006-01-16
E-text prepared by Al Haines
Keywords: Fantasy literature; Fairy tales